COMPUTER-ASSISTED TRANSLATION AND MODERN ISSUES OF TEACHING TRANSLATORS - Victoriya Sibul (PUPIL: International Journal of Teaching, Education and Learning, 2025)
The 21st century has been characterised by new challenges affecting different spheres of human society, different types of art, and different types of professional activity. In the rapidly evolving landscape of the translation industry, Computer-Assisted Translation (CAT) tools have become indispensable. These technologies not only enhance the efficiency and accuracy of translation processes but also significantly influence the way translators are educated and trained. As the demand for skilled translators continues to grow, it is essential to address the modern issues associated with teaching translators in the context of CAT. The present study is concerned with the issue of effective integration of training in new technologies in the education of future translators.